2010
DOI: 10.1186/1472-6793-10-6
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression and activity of digestive proteases in Daphnia: effects of cyanobacterial protease inhibitors

Abstract: BackgroundThe frequency of cyanobacterial blooms has increased worldwide, and these blooms have been claimed to be a major factor leading to the decline of the most important freshwater herbivores, i.e. representatives of the genus Daphnia. This suppression of Daphnia is partly attributed to the presence of biologically active secondary metabolites in cyanobacteria. Among these metabolites, protease inhibitors are found in almost every natural cyanobacterial bloom and have been shown to specifically inhibit Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
121
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(129 citation statements)
references
References 58 publications
7
121
1
Order By: Relevance
“…To our knowledge, this is the first time that different trypsin isoforms have been shown to differ in their responsiveness to dietary proteins for a crustacean species. Differences in trypsin isoform expression have been found in Daphnia magna but in response to protease inhibitors in the diet (Schwarzenberger et al, 2010). It is noteworthy that in the present work, RNA extraction was carried out from tissue biopsies with no regard for the different cell types contained in the digestive gland.…”
Section: Effect Of Dietary Proteins On Trypsin Expressionmentioning
confidence: 99%
“…To our knowledge, this is the first time that different trypsin isoforms have been shown to differ in their responsiveness to dietary proteins for a crustacean species. Differences in trypsin isoform expression have been found in Daphnia magna but in response to protease inhibitors in the diet (Schwarzenberger et al, 2010). It is noteworthy that in the present work, RNA extraction was carried out from tissue biopsies with no regard for the different cell types contained in the digestive gland.…”
Section: Effect Of Dietary Proteins On Trypsin Expressionmentioning
confidence: 99%
“…These proteases production interferes with the grazing ability of some mesozooplankton, e.g. inhibiting Daphnia's digestive proteases [57], leading to the decline of freshwater herbivores in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that the biomass of both large and small filter feeders was significantly negatively correlated with microcystin concentrations, but contrary to our literature-based expectations (Hansson et al, 2007;Sun et al, 2012), it was not the large forms of zooplankton but the small filter feeders that were negatively correlated with the abundance of cyanobacteria (the concentration of Cya). Both daphniids and herbivorous copepods are potential consumers of cyanobacterial cells, but they generally avoid cyanobacteria, because it is a low-quality food item (MartinCreuzburg et al, 2008;Schwarzenberger et al, 2010). Copepods use multiple chemosensory signals in detecting toxins and avoiding their ingestion (Ger et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The cell shape and size of the colonies and the filaments formed by cyanobacteria disturb mechanical aspects of the filtering process, particularly for the large-bodied grazers of the genus Daphnia Cyanobacteria, zooplankton and fish in sub-bloom conditions (DeMott et al, 2001). The absence of sterols and polyunsaturated fatty acids (Martin-Creuzburg et al, 2008) and the production of protease inhibitors (Schwarzenberger et al, 2010) makes cyanobacteria a poor-quality food for zooplankton. Furthermore, the gelatinous or mucilaginous sheath produced by certain cyanobacteria species, e.g.…”
Section: Introductionmentioning
confidence: 99%